PERAN KOMPETENSI DEWAN KOMISARIS DALAM PENGAWASAN PRAKTIK PENGHINDARAN PAJAK DAN MANAJEMEN LABA - Detri Wulandari; Nurul Aisyah Rachmawati (Jurnal Penelitian Akuntansi (JPA), 2021)
This study aims to examine the effect of the competency of the boards on the relationship between tax avoidance and earnings management. This study separates the board’s competencies in accounting and finance. Using a sample of listed manufacturing firms in the Indonesia Stock Exchange from 2014 to 2017, we hypothesized that the board of commissioner’s competencies in accounting or finance weakens the positive relationship between tax avoidance and earnings management. The results provide evidence which is consistent with the hypotheses.